Efecto de la Averrhoa carambola L. o "carambola" vs. gemfibrozilo sobre el perfil lipídico en Rattus rattus var albinus - Castillo Minaya, Karen Yanet; Castillo Minaya, Estalin Humberto; Huamán Saavedra, Juan Jorge (2013)
Introducción: Dyslipidemia represent a primary risk factor for coronary heart disease. Objectives: Compare the effect on the lipid profile between Averrhoa Starfruit, "Starfruit" versus Gemfibrozile in Rattus rattus var albinus. Material and Methods: A randomized study was realized. I worked with 39 Rattus rattus var albinus male; were divided in 2 experimental groups and a group control (GC). They were put under stage of preparation by 2 weeks, alter that, they were feeding with a rich fat diet (PIG) for 2 weeks; later I administered Starfruit and Gemfibrozile to experimental groups (GE1 and GE2, respectively). The lipid profile in each stage was measured and it was applied to the Test of Variance Analysis and test of Duncan. Results: The seric cholesterol level: GC basal 80mg/dL, PIG 97mg/dL, at two week 83 mg/dL. GE1 basal 84 mg/dL, PIG 100 mg/dL, at two week 72 mg/dL(p<0.05). GE2 basal 83 mg/dL, PIG 104mg/dL, at two weeks 80 mg/dL. The seric level of LDL Cholesterol: GC basal 47 mg/dL, PIG 66 mg/dL, at two weeks 50mg/dL. GE1 basal 46mg/dL, PIG 65 mg/dL, at two weeks 39 mg/dL (p<0.05). GE2 basal 47 mg/dL, PIG 71 mg/dL, at two weeks 42 mg/dL. The seric level of Triglycerides and The seric level of HDL Cholesterol was not significantly changes for de starfruit but by gemfibrozile. Conclusions: The Starfruit ingestion significantly diminishes the levels of total cholesterol, cholesterol LDL in Rattus rattus var albinus. Introducción: Las dislipidemias representan un factor de riesgo primario para la cardiopatía coronaria. Objetivo: Comparar el efecto sobre el perfil lipídico entre Averrhoa carambola L. o "carambola" vs el Gemfibrozilo en Rattus rattus var albinus. Material y Métodos: Se realizó un estudio aleatorizado. Se trabajó con 39 Rattus rattus var albinus machos; divididos al azar en 2 grupos experimentales (GE) y un grupo control (GC). Sometidos a 2 semanas de acondicionamiento, 2 semanas de alimentación rica en grasa (PIG); posteriormente se administró carambola y Gemfibrozilo a grupos ...